Imaging High-Risk Atherothrombosis Using a Novel Fibrin-Binding Positron Emission Tomography Probe. Issue 2 (February 2022) - Izquierdo-Garcia, David; Diyabalanage, Himashinie; Ramsay, Ian A.; Rotile, Nicholas J.; Mauskapf, Adam; Choi, Ji-Kyung; Witzel, Thomas; Humblet, Valerie; Jaffer, Farouc A.; Brownell, Anna-Liisa; Tawakol, Ahmed; Catana, Ciprian; et al.
Abstract : Background and Purpose: High-risk atherosclerosis is an underlying cause of cardiovascular events, yet identifying the specific patient population at immediate risk is still challenging. Here, we used a rabbit model of atherosclerotic plaque rupture and human carotid endarterectomy specimens to describe the potential of molecular fibrin imaging as a tool to identify thrombotic plaques. Methods: Atherosclerotic plaques in rabbits were induced using a high-cholesterol diet and aortic balloon injury (N=13). Pharmacological triggering was used in a group of rabbits (n=9) to induce plaque disruption. Animals were grouped into thrombotic and nonthrombotic plaque groups based on gross pathology (gold standard). All animals were injected with a novel fibrin-specific probe 68 Ga-CM246 followed by positron emission tomography (PET)/magnetic resonance imaging 90 minutes later. 68 Ga-CM246 was quantified on the PET images using tissue-to-background (back muscle) ratios and standardized uptake value. Results: Both tissue-to-background (back muscle) ratios and standardized uptake value were significantly higher in the thrombotic versus nonthrombotic group ( P <0.05). Ex vivo PET and autoradiography of the abdominal aorta correlated positively with in vivo PET measurements. Plaque disruption identified by 68 Ga-CM246 PET agreed with gross pathology assessment (85%). In ex vivo surgical specimens obtained from patients undergoing elective carotid endarterectomy (N=12), 68 Ga-CM246 showed significantly higher binding to carotid plaques compared to a D-cysteine nonbinding control probe. Conclusions: We demonstrated that molecular fibrin PET imaging using 68 Ga-CM246 could be a useful tool to diagnose experimental and clinical atherothrombosis. Based on our initial results using human carotid plaque specimens, in vivo molecular imaging studies are warranted to test 68 Ga-CM246 PET as a tool to stratify risk in atherosclerotic patients. Abstract : Supplemental Digital Content is available in the text.